Emotional violence and maternal mental health: a qualitative study among women in northern Vietnam - Trần Thơ Nhị; Nguyễn Thị Thúy Hạnh; Tine M. Gammeltoft (BMC, 2018)
Abstract Background Worldwide, intimate partner violence (IPV) during pregnancy is a pressing and prevalent public health problem. Existing research has found close associations between IPV and perinatal mental health, yet little is known about women's own perceptions of these associations. This study aimed to explore Vietnamese women's experiences of emotional partner violence and their perceptions of the implications of such violence for their mental health. Methods The data were collected through in-depth interviews with 20 women living in Hanoi, Vietnam who had reported exposure to emotional partner violence and attained high depression scores in a prospective cohort study. Ten women were pregnant and ten had recently given birth. The data were analysed by qualitative content analysis. Results The women described emotional partner violence as a major life stressor. Their accounts pointed to three particularly significant dimensions of emotional violence: being ignored by the husband; being denied support; and being exposed to controlling behaviours. These experiences affected the women's sense of wellbeing profoundly, causing sadness and distress. The women's accounts indicated that experiences of emotional violence were significantly shaped by dominant kinship arrangements: practices of patrilocal residence and principles of patrilineal descent tended to aggravate women's vulnerabilities to partner violence. Conclusions This qualitative study from Vietnam documents close associations between emotional partner violence and perinatal distress, while also pointing to kinship arrangements as particularly significant structural contexts shaping women's experiences of partner violence. The study findings suggest that effective policies and programs to decrease women's vulnerability to intimate partner violence must take into account the kinship arrangements that prevail in a given society.